FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREEKLAMPSIA PADA IBU BERSALIN DI RSUD SITI AISYAH KOTA LUBUKLINGGAU - Pitri Subani; Netty Herawati; Lila Sari Basri (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
The purpose of this study studied the factors associated with the incidence of Preeclampsia in maternal mothers at Siti Aisyah Hospital Lubuklinggau. Type of research used in this research is analytic survey with case control approach. The population of this study were all maternal mothers recorded in the register of maternity mother at Siti Aisyah Hospital Lubuklinggau which amounted to 1860 labor. Samples were taken in total sampling ie maternal mother with preeclampsia incident that is 198 cases and as control taken as many as 198 respondents from 1662 mothers in Siti Aisyah Hospital that is using method comparison 1: 1. Data analysis was performed by univariate, bivariate analysis.The results of the study were: (1) There were (65.9%) aged between 20-35 years, (2) There was (58.6%) multiparous parity and (3) There was (59.3%) gestational distance ≥ 2 years and 5 years. (4) There was a significant relationship between age and preeclampsia occurrence. (5) There is a significant relationship between parity and the occurrence of preeclampsia. (6) There was a significant association between pregnancy distance and the incidence of preeclampsia in Siti Aisyah Hospital Lubuklinggau. Keywords : age, gestational distance, parity,,preeclampsia incidence